2023
DOI: 10.1007/s00374-023-01714-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phosphorus availability in paddy soils: the importance of integrating soil tests and plant responses

Abstract: Phosphorus (P) cycling in paddy soil is closely related to iron (Fe) redox wheel; its availability to rice has thus generally been ascribed to Fe minerals reductive dissolution. However, the literature aimed to identify the best method for predicting rice available P does not uniformly point to Fe reductants. Rice plants can indeed solubilize and absorb P through many strategies as a function of P supply, modifying the chemical environment. Therefore, this study aims to estimate P availability in paddy soils c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…In general, the differences in crop production can be attributed to P availability in soils [4,34]. In this study, the concentration of available P determined for CF paddies was higher than ID paddies, primarily due to the enhanced reductive dissolution of P-bearing minerals in flooded paddies [4,34]. However, the level of P in these paddies satisfies the required level (e.g., 13.5 mg kg −1 ) for rice paddies recommend by Korean RDA.…”
Section: Rice Yieldmentioning
confidence: 58%
See 1 more Smart Citation
“…In general, the differences in crop production can be attributed to P availability in soils [4,34]. In this study, the concentration of available P determined for CF paddies was higher than ID paddies, primarily due to the enhanced reductive dissolution of P-bearing minerals in flooded paddies [4,34]. However, the level of P in these paddies satisfies the required level (e.g., 13.5 mg kg −1 ) for rice paddies recommend by Korean RDA.…”
Section: Rice Yieldmentioning
confidence: 58%
“…Similarly, Liu et al [7] showed with meta-analysis data that the intermittent drainage has no effect on rice yield as long as the SOC level and N content (e.g., 50 kg N ha −1 ) are sufficiently high, due to the enhanced decomposition of SOC in drained paddy. In general, the differences in crop production can be attributed to P availability in soils [4,34]. In this study, the concentration of available P determined for CF paddies was higher than ID paddies, primarily due to the enhanced reductive dissolution of P-bearing minerals in flooded paddies [4,34].…”
Section: Rice Yieldmentioning
confidence: 63%
“…Unsur P dapat memacu peningkatan efisiensi kerja kloroplas dalam daun yang berperan dalam suplai dan transfer energi pada seluruh proses biokimia (Booromand & Grough, 2012). Selain itu unsur P juga berperan dalam mendukung pertumbuhan padi mulai dari awal pertumbuhan vegetatif sampai fase pembentukan bunga dan pematangan biji (Ye et al, 2019;Martinengo et al, 2023).…”
Section: Kandungan Klorofilunclassified
“…The availability of P in paddy soils is strongly driven by redox conditions, although the higher soil solution P concentrations under reducing conditions do not necessarily result in a higher plant P uptake (Martinengo et al 2023). Previously, low P uptake by rice has been attributed to high P sorption capacity of newly formed Fe minerals near the root surface (Zhang et al 2003;Kirk 2004;Veelen et al 2020).…”
Section: Introductionmentioning
confidence: 99%